Dysplasia and carcinoma in longstanding ulcerative colitis: an endoscopic and histological surveillance programme. Issue 12 (December 1991) - Leidenius, M; Kellokumpu, I; Husa, A; Riihelä, M; Sipponen, P
Abstract : From 1976 to 1989 a total of 66 patients with longstanding ulcerative colitis were entered in a colonoscopic surveillance programme in order to detect dysplasia. Thirty patients had extensive or total ulcerative colitis and 36 left sided colitis. The median duration of the disease at the end of the follow up was 15.0 years. Altogether 182 colonoscopies (2.8 per patient), each involving approximately 20 biopsies from different sites of the colon, were performed. In the total or extensive colitis group, five patients had low grade and one patient had high grade dysplasia. In the left sided colitis group, three patients had low grade dysplasia. In three patients low grade dysplasia was detected in a macroscopic lesion or mass of colonic mucosa. Sixty per cent of the dysplasia specimens were from the right colon. The incidence of dysplasia was higher in patients with extensive colitis and increased with the duration of the disease. None of the patients have so far developed colorectal carcinoma. Our results indicate that a colonoscopic surveillance programme is a safe alternative to prophylactic colectomy in longstanding ulcerative colitis.